Parâmetros genéticos para características indicadoras de eficiência reprodutiva e produtiva de ovinos da raça Santa Inês - Ono, Rafael Keith [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Reproductive efficiency traits are of significant economic importance as they relate to the source income of sheep meat enterprise. Reliable genetic parameters are essential for selection index design and to determine the correlated response to selection that will occur in other traits in a selection index. Thus, the aim of this study was to estimate (co)variance components and parameter genetics for reproductive traits in Santa Inês sheep. Data included records of 4,742 Santa Inês sheep from Santa Inês Breeding Program of Sergipe State Sheep and Goats Breeders Association and University of São Paulo. In the first part, studied traits were age at first lambing (AFL), Lambing Interval (LI), Litter size at birth per ewe lambing(LSB), Litter size at weaning per ewe lambing and Ewe rearing ability per ewe lambing (RA) defined as lambs weaned per lamb born. The (co)variance components were estimated by bivariate analysis using Gibbs sampling methodology with THRGIBBS1F90 software and number of iterations, length of burn-in and sampling interval were 1,500,000, 500,000 and 250, respectively. For AFL and LI, a linear model was applied and for LSB, LSW and RA, a threshold model. Posterior means of heritability were 0.239 ± 0.053 for AFL, 0.056 ± 0.022 for LI, 0.098 ± 0.047 for LSB, 0.016 ± 0.01 for LSW and 0.019 ± 0.011 for RA. Posterior means of genetic correlation among reproductive traits ranged from -0.62 between LSB and RA to 0,82 between LSW and RA. Posterior means of phenotypic correlation between AFL and LI and each one among the others were low, close to zero. The phenotypic correlation were positive and medium between LSB and LSW (0.44 ± 0.02), medium and negative between LSB and RA (0.37 ± 0.02) and were high and positive between LSW and RA (0.98 ± 0.00). Reasonable genetic progress can be obtained in sexual precocity using age at first lambing as selection criteria. Large influences of environmental effects on LI, LSB ...

As características ligadas à eficiência reprodutiva são as que apresentam maior valor econômico na maioria dos sistemas de criação de carne ovina, pois estão intimamente ligadas à disponibilidade do produto final. Estimativas confiáveis de parâmetros genéticos são essenciais para a definição de índices de seleção e para determinar a resposta correlacionada sobre as demais características presentes no índice de seleção. Assim, esse trabalho teve por objetivo estimar componentes de (co)variância e parâmetros genéticos para características reprodutivas em ovinos da raça Santa Inês. Foram utilizados dados de 4.742 ovelhas pertencentes ao Programa de Melhoramento Genético da raça Santa Inês da Associação Sergipana de Criadores de Caprinos e Ovinos em parceria com a Universidade de São Paulo. Para o estudo foram consideradas as características: Idade ao primeiro parto (IPP), Intervalo de partos (IDP), Número de cordeiros nascidos por ovelha parida (NCN), Número de cordeiros desmamados por ovelha parida (NCD) e Habilidade de criação por ovelha parida (HC) definido como a razão entre NCN e NCD. Os componentes de (co)variância foram estimados por meio de análises bivariadas, sob modelo animal linear para IPP e IDP e limiar (threshold) para as demais características, utilizando o método da amostragem de Gibbs do programa THRGIBBS1F90. O número de iterações, tamanho do descarte e intervalo de descarte considerados foram 1.500.000, 500.000 e 250, respectivamente. As herdabilidades estimadas à posteriori foram de 0,239 ± 0,053 para IPP, 0,056 ± 0,022 para IDP, 0,098 ± 0,047 para NCN, 0,016 ± 0,01 para NCD e 0,019 ± 0,011 para HC. As correlações genéticas estimadas à posteriori entre as características variaram -0,62 entre NCN e HC a 0,82 entre NCD e HC. As correlações fenotípicas à posteriori entre IPP e IDP e cada uma com as demais características foram de baixa magnitude, próximas a...
Keywords: Ovino; Estimativa de parametro; Cordeiro; Animais - Seleção; Genetica animal; Sheep